ANALISIS PENGUASAAN KATA KERJA â€œQU BIEâ€ DAN â€œFEN BIEâ€ PADA MAHASISWA 2016 BAHASA MANDARIN UNTAN - Indrayani, Stevi; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVerbs are one of the most commonly used syntax in Chinese expression and important materials in Chinese teaching. For example, verbs